Waste Stabilisation Ponds - Von Sperling, Marcos (Biological Wastewater Treatment Series, 2007)
"Waste Stabilisation Ponds is the third volume in the series Biological Wastewater Treatment. The major variants of pond systems are fully covered, namely: facultative ponds anaerobic ponds aerated lagoons maturation ponds The book presents in a clear and informative way the main concepts, working principles, expected removal efficiencies, design criteria, design examples, construction aspects, operational guidelines and sludge managment for pond systems. About the series: The series is based on a highly acclaimed set of best selling textbooks. This international version is comprised by six textbooks giving a state-of-the-art presentation of the science and technology of biological wastewater treatment. Other titles in the series are: Volume 1: Waste Stabilisation Ponds Volume; 2: Basic Principles of Wastewater Treatment; Volume 4: Anaerobic Reactors; Volume 5: Activated Sludge and Aerobic Biofilm Reactors; Volume 6: Sludge Treatment and Disposal"